GLOBAL COVID-19: WHAT ISLAMIC ECONOMIC AND FINANCE CAN DO? INDONESIA EXPERIENCE - Iskandar, Azwar; Possumah, Bayu Taufiq; Aqbar, Khaerul (UNISSULA, 2021)
Pandemic of COVID-19 has shocked and spread all over the world, including Indonesia. This research was conducted with the aim to lay out the role of Islamic economic and finance policies, as well as to propose a number of solutions which could be offered to solve various problems in time of the COVID-19 pandemic in Indonesia. By using descriptive qualitative approach, this research attempts to analyse various concepts that found in the research process trough content analysis techniques and library research. The results show that within the framework of Islamic economic and finance, some strategies that we can employ to dispose the social impact of COVID-19 such as: (1) distribution of direct cash assistance from zakat and infaq, collected by zakat and other social institutions; (2) strengthening infaq programs for various needs; (3) strengthening waqf programs, including cash waqf for social waqf projects, productive waqf, combination of social-productive waqf, or cash waqf linked sukuk; (4) superior venture capital assistance for the business sectors or Micro and Small Enterprises (MSEs); (5) the qardh al-hasan scheme; (6) strengthening MSMEs businesses; (7) improvement of Islamic economic and finance literacy; and (8) the development of Islamic financial technology. If the above programs using Islamic economic and finance instruments could really be encouraged, the economic surplus would be re-established and the acceleration of economic recovery could be realized, while at the same time reducing poverty and supporting the achievement of equitable distribution of income and wealth.